PROSEDUR PENGAJUAN DAN MEKANISME PENGUJIAN RESTITUSI PAJAK PERTAMBAHAN NILAI - Laksono, Tri Jati; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Business practitioners in the business development particularly in the field of constructions businessservice often experience problem in their cash flow, because some of their customers are the appointed partiesin which their tax to be collected by the regulation of the minister of finance no. 85 of 2012. The limitedcapability in the preparation of administration and cost which is supposed to be used to pay experts andprimary materials have made business practitioners to make credit decision. Some of these businesspractitioners even consider that the overpayment restitution will take a lot of time and costs so theoverpayment which is caused by the collection of value added tax by the tax collector is better be chargedon cost of goods sold.The result of the research shows the submission procedures and the examinationmechanism so the business practitioners can find out the formal test and what documents have to beprepared for the application of restitution. The restitution can become a financial solution when theapplication of restitution has been granted. No matter how big the cost that has become the value of taxbills, the restitution will be granted and the tax arrear which has been obtained will be directly subtractedfrom the overpayment of the value added tax which has been restitutioned.Keywords: restitution, restitution application procedures, application of restitution mechanisms,restitution can be a financial solution, no charged restitution.